Assessing Debt Sustainability in a Stochastic Environment: 200 years of Dutch Debt and Deficit Management - Sweder van Wijnbergen; Alexander France (Tinbergen Institute, 2012)
When debt levels approach critical levels, tax payers may revolt against the associated debtservice burden. Funding problems may arise in capital markets when lenders anticipate such revolts and refuse to participate in debt auctions. We provide a stochastic framework to assess whether such problems may arise and argue that the key to fiscal sustainability in a stochastic environment is a feedback rule from debt level shocks back to corresponding adjustments in the primary surplus. We show that such feedback rules narrow future distributions of debt-output ratios and so reduce crisis probabilities. We apply the methodology to Dutch debt and deficit data spanning two centuries. Our results strongly argue for the incorporation of rules stipulating tightening fiscal policy whenever debt stocks exceed previously agreed upon targets (like in the original Eurozone Stability pact).
Keywords: E62; H62; H63; H68; 330; deficits; debt sustainability; fiscal rules